Prevalence of Quinolone susceptible Pseudomonas aeruginosa and Staphylococcus aureus in Delayed healing DFU's in Ekpoma, Nigeria - Agwu, Ezera (Int Wound J, 2010)
Aim. To investigate the prevalence and antibiogram of Pseudomonas aeruginosa and Staphylococcus aureus from delayed-healing foot ulcers among patients with diabetes in Ekpoma. Methods. Using standard aseptic microbiological methods, 220 delayed-healing diabetic foot ulcer samples were analyzed for bacteria isolation, identification, and susceptibility before and 12 weeks after antibiotic administration. Chi-squared (α = 0.01) was used to test for statistical significance. Results. Out of the 220 samples analyzed, 181 (82.3%) were infected (P aeruginosa [41.8%]; S aureus [30%]; co-infection of P aeruginosa and S aureus [10.5%]). Wound healing was significantly (P < 0.01) dependent on the presence of P aeruginosa and S aureus in the study population. S aureus and P aeruginosa showed the highest (74.2% and 71.3%, respectively) and lowest (38.2% and 34.8%) susceptibilities to levofloxacin and sparfloxacin, respectively. P aeruginosa was 68.7% susceptible to rifampicin; 53% to erythromycin, 52.2% to vancomycin; 38.3% to ceftriazone; 36.5% to cefuroxin; and 32.2% to oxacillin. S aureus was 51.7% susceptible to rifampicin, 37.1% to cefuroxin; 33.7% to ceftriazone; 28.1% to vancomycin; and 25.8% to oxacillin. Twelve weeks after antibiotic administration, 54% of samples had no growth and showed accelerated wound healing; 26.7% yielded P aeruginosa, while 19.3% yielded S aureus. Conclusion. Delayed-healing diabetic foot ulcers in Ekpoma are colonized by levofloxacin- and sparfloxacin-susceptible P aeruginosa and S aureus. Microbial load reduction due to appropriate antibiotic administration contributed to the acceleration of the wound healing process for 54% of patients who participated in the follow-up procedures. Surveillance with improved diagnostic facilities is recommended. Address correspondence to: Ezera Agwu, PhD Medical Microbiology & Parasitology, School of Health Sciences Kampala International University, Western Campus, Ishaka Box 71, Bushenyi
Keywords: Quinolone; Staphylococcus aureus; Pseudomonas aeruginosa